Nutrition and Epidemiologic Transition on Body Composition and Dietary Pattern of Indigenous Children and Adolescents in Peninsular Malaysia (Bangladesh Journal of Nutrition, 2021)
Malaysia has been undergoing rapid nutrition and drastic epidemiologic transition over the past two decades. This has resulted in the evolution of synergistic existence between undernutrition, overnutrition and hidden hunger. The indigenous population of Malaysia known as Orang Asli continues to experience hunger pandemic in spite of industrialisation and economic growth. The objective of this study was to appraise the impact of nutrition and epidemiologic transition among indigenous children and adolescents. A cross-sectional study was carried among Semai Orang Asli children and adolescents (6-18 years) in Perak. Population Proportion to Size (PPS) was adopted to the sample size samples (N=747) representative of all districts in Perak. Demographic and socio-economic profile was collected using a pre-tested questionnaire, anthropometric measurements were recorded using World Health Organization standard protocols and 24- hour recall method was used to appraise the dietary pattern. Physical signs and symptoms for nutritional deficiencies were done with the help of trained public health nurses. The results were analyzed using SPSS22.0 software to establish possible associations. The findings showed that the incidence of underweight (2%) and malnutrition has declined significantly, with the emerging trends of overweight (19%) and obesity (0.7%) among school children and adolescents. Protein and Energy Malnutrition, Vitamin A, iron and iodine deficiencies, and dental fluorosis were commonly present among the study population. Poor inclusion of fruits and vegetables, legumes, and dairy foods leads to poor dietary diversity among these children. Nutrition and the epidemiologic transition has had a profound impact even on the indigenous population which warrants immediate attention and intervention.Bangladesh J. Nutr. Vol. 34, December 2020, P: 41-53